Role of altered IL‐33/ST2 immune axis in the immunobiology of Guillain‐Barré syndrome. (12th April 2022) - Sharma, Praveen P.; Seshagiri, Doniparthi V.; Nagappa, Madhu; Mullapudi, Thrinath; Sreenivas, Nikhitha; Dey, Saikat; Shivaram, Sumanth; Wahatule, Rahul; Kumawat, Vijay; Sreekumaran Nair, Binu V.; Kamath, Sriganesh; Sinha, Sanjib; et al.
Abstract: Background: The IL‐33/ST2 immune axis plays crucial roles in infection and immunity. A dysregulated IL‐33/ST2 axis can induce autoimmune reaction and inflammatory responses. Guillain‐Barré syndrome (GBS) is an acute peripheral neuropathy, mostly caused by post‐infection autoimmunity. The role of IL‐33/ST2 axis is not known in GBS. This study aimed to explore the role of IL‐33/ST2 axis in GBS. Methods: Three single nucleotide polymorphisms (SNPs) of Il33 gene (rs16924159, rs7044343, rs1342336) and three SNPs of Il1rl1 gene (rs10192157, rs1041973, rs10206753) coding for suppressor of tumorigenicity 2 (ST2) were genotyped in 179 GBS patients and 186 healthy controls by TaqMan Allelic Discrimination Assay. Plasma levels of IL‐33 and sST2 were measured in a subset of GBS patients ( n  = 80) and healthy controls ( n  = 80) by ELISA. Results: The frequencies of CC genotype of rs10192157 ( p  = 0.043) and TT genotype of rs10206753 ( p  = 0.036) SNPs of Il1rl1 gene differed significantly between GBS patients and healthy controls. Gene–gene interaction between Il33 and Il1rl1 genes also conferred significant risk for GBS. In addition, the plasma sST2 levels were significantly elevated in GBS patients compared to healthy subjects (24, 934.31 ± 1.81 pg/ml vs. 12, 518.97 ± 1.51 pg/ml, p  < 0.001). Plasma sST2 levels showed a significant correlation with the disability scores at the peak of neurological deficit in GBS patients. Conclusions: The IL‐33/ST2 axis is suggested to influence the immunopathogenesis of GBS. Genetic variants of Il1rl1 gene might serve as a risk determinant of GBS and plasma sST2 levels might emerge as a biomarker of severity of GBS, if replicated further by other studies. Abstract : We demonstrate significantly elevated plasma soluble suppressor of tumorigenicity 2 (sST2) levels in a large cohort of Guillain‐Barré syndrome (GBS), and these elevated levels correlate with worse disability and requirement for mechanical ventilation. Polymorphic variants of Il1rl1 gene and gene–gene interaction between Il33 and Il1rl1 genes also conferred increased risk for developing GBS. The current study for the first time adds new knowledge on the important implications of altered IL‐33/ST2 axis in GBS pathobiology. The elements of IL‐33/ST2 axis may emerge as important biomarkers for predicting risk and severity of GBS. This may also lead to targeted therapy for ameliorating the severity of GBS.